2020
DOI: 10.2174/2213335607666200129113827
|View full text |Cite
|
Sign up to set email alerts
|

Alumina-K3PO4 Solid Supported Microwave Synthesis of 1, 3-diaryl-2- propene-1-one Derivatives as a Prominent Antioxidant Scavenger

Abstract: Background: The various industrial processes have diverse effect on environment through pollution. In view of these observations, some environmentally benign synthetically protocols have developed under green chemistry. For rapid and sustainable synthesis the microwave irradiation (MI) has gained popularity as a powerful tool compared to conventional synthesis. The present study describes the synthesis of novel substituted 1, 3-diaryl-2-propene-1-one derivative using alumina supported K3PO4-MWI combination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The presence of α,β-unsaturated carbonyl system makes chalcone huge important in organic chemistry. 10 The versatility of chalcones arises from their distinctive combination of functional groups. Chalcone and their derivatives can act as chelating agents towards metals to form stable complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of α,β-unsaturated carbonyl system makes chalcone huge important in organic chemistry. 10 The versatility of chalcones arises from their distinctive combination of functional groups. Chalcone and their derivatives can act as chelating agents towards metals to form stable complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al reported the series of chalcone derivatives 109 a-n (Figure 19) by microwave-assisted method. [158] Some of these substances were discovered to be substantial scavengers and showed stronger antioxidant activity. The results showed that the IC 50 By using the two-directional Claisen-Schmidt condensation, numerous novel bis-hydroxy derivatives of chalcones 110 a-h (Figure 19) were produced by Khazaei-Poul et al [159] The in vitro antioxidant activity of bis-hydroxychalcones was measured using DPPH radical scavenging activity, with IC 50 values ranging from 134 to 1626 μM compared to ascorbic acid.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Patil et al . reported the series of chalcone derivatives 109 a – n (Figure 19) by microwave‐assisted method [158] . Some of these substances were discovered to be substantial scavengers and showed stronger antioxidant activity.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The use of catalyst for the synthesis of imine suffers from several demerits such as harsh reaction conditions, tedious work up in the separation of product and catalyst. Recently the use of K3PO4 13 encouraged us to use it for the syntheses of imines in combination with microwave irradiation methods. The tripottasium phosphate faces the reaction between 2-amino pyridine and different substituted benzaldehyde to give Schiff bases (Scheme 1).…”
Section: Chemistry and Synthesismentioning
confidence: 99%
“…12 Therefore, this technique presently known as etechnique as easy, ecofriendly, environmentally being and economic. 13 Following these observations and with the aim of our research has concerned on achieving reasonable yields of the synthesized Schiff bases from 2-aminopyridine. In the present work we plan to synthesize novel series of Schiff bases (3a to 3l) derived from 2-amino pyridine with different substituted benzaldehydes by using alumina-anhydrous tripottasium phosphate under microwave irradiation.…”
Section: Introductionmentioning
confidence: 96%